On Investigation Of Academic Discourse - Shirkhan Gizi, Hamidova Nigar (Advances in Social Sciences Research Journal, 2017)
The article deals with the investigations of academic discourse. The definition of discourse and text, as well as the explanation of academic discourse, research questions, and the comparison about the stated problem are presented in the article. The author presents her attitude toward various definitions of academic discourse. For instance, cited by A.Weidman and R.Patterson the academic discourse is analyzed like this: “Academic discourse, which is historically grounded, includes all lingual activities associated with academia, the output of research being perhaps the most important. The typicality of academic discourse is derived from the unique distinction making activity which is associated with the analytical or logical mode of experience (Weideman 2006, p.81-101). The scientists consider academic discourse to be more than grammar. It is the kind of discourse which has its functions such as exposition, clarification, and conclusion. Academic discourse requires the doers to perform things with language like explanation, definition, comparison, contrast, classification, agreement, disagreement, illustration, elaboration, making claims, seeing implications, inference, exemplifying, anticipating, and conclusion. The article states that this kind of discourse has also its cognitive and analytical processing. The competence is considered to be handling academic language is far more the “skills” of listening, speaking, reading, and writing. Academic discourse encourages the participants to do something about low levels of academic literacy, and in this case a participant should be able to measure that ability accurately and reliably. It is because of that academic discourse is a complex ability which encompasses many subcomponents; a language test that is multifaceted is preferable to a monotone test design and is likely to be more reliable. It is necessary to mention that language courses can be applied to improve academic literacy (Weidman 2014, p.13-22). The three theories such as the speech act theory by Austin and Searle, the frame theory by Goffman and Tannen and the politeness theory by Brown and Levinson have been touched upon in the article as well.